Pendampingan Kepada Kelompok Wanita Tani (KWT) Mawar Dalam Budidaya Tanaman Sayuran Untuk Meningkatkan Ekonomi Masyarakat - Dian Intan Tangkeallo; Dwibin Kannapadang; Rati Pundissing; Chrismesi Pagiu; Randi Tangdialla (BADAN PENERBIT STIEPARI PRESS, 2021)
Vegetable cultivation is quite a large sector in agriculture. Tondon Mamullu Village, Makale District has a women farming group (kwt) called KWT Mawar, and concentrates on vegetable cultivation. This group of women rose farmers have the potential to progress in their cultivation field, but the lack of motivation, limited knowledge of cultivation and continuity of cultivation as well as limited marketing are obstacles in the cultivation process, so they need to be given a little direction from university stakeholders to be able to dedicate their knowledge to the community. The long-term objectives of this program are: (1) Encouraging the growth of motivation and creativity of the Mawar Bodas kwt in the plant cultivation process so as to increase production, (2) Helping the Mawar kwt's potential in developing cultivation with maximum production, and (3) Assisting the Mawar kwt in solving problems in cultivation. The specific target to be achieved is the production of several types of vegetables.